ANALISIS PENGARUH JUMLAH ANGGOTA, SIMPANAN ANGGOTA, DAN PIUTANG ANGGOTA TERHADAP SISA HASIL USAHA PADA PRIMKOPKAR MANUNGGAL DAMATEXTIMATEX SALATIGA - Meannita Dipa Anindyatama; Kusmayadi Kusmayadi Kusmayadi; Lilis Mardiana Anugrahwati (Politeknik Negeri Semarang, 2019)
t:Declining the number of members caused by desicion of company to make termination of employment and make number of members decline. This problem also take effect for member’s participation for cooperative. Based on analysis the effect of number of members, equity of members, and member receivable as independent variables which are indicating of member’s partisipation, give a result that the analysis of all the independet variables do not make a significant effect for the income of Primkopkar Manunggal Damatex-Timatex Salatiga. This caused by the problems in cooperative which make number of members, equity of members, and member receivable do not affect the cooperative income.